Understanding the changing notions of centre-state financial relations under the GST regime - Dahiya, Rinki, and Dahiya, Priya (Bihar Journal of Public Administration)
It was believed that India$1 (Bs growth is hampered by a complex array of stateby-state tax codes that hinder the ease of doing business across state borders and thereby hindrances in even economic growth. The passing of the 101 Constitutional Amendment Act, 2016 has paved the way for GST regime in India. GST is widely viewed as an innovation that will allow the authorities to create a more unified economy which will change the trajectory of growth. It was expected that the states that are not financially strong will get an opportunity to gain revenue. On the contrary, critics argue that it will hamper the Indian co-operative federalism as it leads the states to lose its control over financial autonomy and its implementation will be problematic for India$1 (Bs small businesses and, perhaps more importantly, undermine public trust in the GST. It has added new dimensions to Centre-state relations. It is against this background, the paper pertinent to analyze some of these pressures that have strained Centre-state relations in the past few decades and to find out what type of measures are needed to fundamentally altered the deep inequality in financial relations. The paper also highlights some of the important concerns that the new GST regime has raised and to examine how and to what extent GST could be a template for the future of cooperative s
Keywords: GST(goods and services tax), Federalism, Constitution, Centre-state relations, Tax reform, India